The Role of International Law in Combating the Crime of Piracy in High seas - Zain, Zakaria AbdelWahab Mohammed; Elzein, Ahmed Mohmed Ahmed (Journal of Economic, Administrative and Legal Sciences, 2022)
The study dealt with the crime of maritime piracy, and it included two sections. The first topic dealt with the concept of the crime of maritime piracy and its legal adaptation, while the second touched on the global judicial jurisdiction in combating the crime of maritime piracy. Alluding to the slackness in combating the crime of maritime piracy, the phrases related to the definition of the crime of maritime piracy contained in international conventions should be controlled and unified so that there is no conflict in their interpretation.
Keywords: Regional jurisdiction; Combating the crime of maritime piracy; international jurisdiction; High seas